Bevacizumab and Weekly Docetaxel in Patients with Metastatic Castrate-Resistant Prostate Cancer Previously Exposed to Docetaxel. (21st August 2011) - Francini, Filippo; Pascucci, Alessandra; Francini, Edoardo; Bargagli, Gianluca; Conca, Raffaele; Licchetta, Antonella; Roviello, Giandomenico; Martellucci, Ignazio; Chiriacò, Giorgio; Miano, Salvatora Tindara; Marzocca, Giuseppe; Manganelli, Antonio; et al.
Abstract : Background . The aim of this paper was to evaluate the activity and tolerability of docetaxel (D) and bevacizumab (Bev) in patients with metastatic castrate-resistant prostate cancer (CRPC) previously exposed to D. Methods . Treatment consisted of D 30 mg/m 2 i.v. for four consecutive weekly administrations followed by a 2-week rest interval, in addition to Bev 5 mg/kg i.v. every 2 weeks. Results . Forty-three patients were enrolled: a PSA response was observed in 27 patients (62.7%, 95% CI: 0.41 to 0.91), and a palliative response was achieved in 31 patients (72.1%, 95%CI: 0.48 to 1.02). After a median followup of 11.3 months, only five patients had died. The regimen was generally well tolerated. Conclusion . Weekly D + biweekly Bev seems to be an effective and well-tolerated treatment option for patients with metastatic CRPC previously exposed to D-based chemotherapy.